Perilaku Pencarian Informasi Covid-19 Pada Masyarakat Daerah Sindang Sari Kecamatan Panyileukan Kota Bandung - Indah, Rosiana Nurwa; Fadhli, Rahmat; Achmad Syam, Rifqi Zaeni (Baitul 'Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2022)
This study aims to determine the information seeking behavior of Covid-19 and the obstacles faced by the people of the Sindang Sari area, Panyileukan District, Bandung City. This research uses descriptive qualitative research. The informants in this study were 5 residents of the Sindang Sari area, Panyileukan District, Bandung City. Collecting data through observation, literature study, documentation and interviews. Data analysis using data collection, data reduction and drawing conclusions. The results obtained indicate that the pattern of information search for the people of the Sindang Sari area, Panyileukan District, Bandung City is influenced by a person's psychological factors, demographics, one's role in society, the environment, and the characteristics of available information sources according to Wilson's theory. As for the obstacles faced when searching for information, namely the presence of anxiety and fear after accessing information about Covid-19; ignorance in determining reliable information; terms related to Covid-19; less stable signal; and social distancing policies that limit informants.